A multiculturalidade nas políticas educacionais e a formação de professores : Brasil e Portugal - Araujo, Viviane Patricia Colloca (2009)
In this work trying to understand how the education politics and of teachers' formation, in Brazil and in Portugal, they are attending to the present multiculturalidade in these countries. For this, I use the documentary inquiry for the gathering of the data and the analysis of content to describe and to understand these collected data. I carried out the collection of the data at two moments: the data of Portugal were collected in 2006, through a traineeship in the Faculty of Psychology and of Sciences of the Education of the University of Oporto and the data of Brazil were collected in the beginning of 2008. Besides the analysis of the documents also interviews were used semi-structured to understand the politics of teachers' formation and the actions implemented by the Brazilian and Portuguese Ministries of Education. In this form, I structured this work in three parts. In the first part I situates the theoretical referential system and methodology of the Theory, subdivided in four chapters. Firstly, I think about the context of the globalization and his impacts about the economy, about the politics, about the culture and, principally, about the education through the education politics. Next, I discuss the key concepts of the theoretical referential system and connect these concepts with the education of a general form. In the third chapter, I talk about the teachers' formation in front of the multicultural questions and the possible strategies to re-structure the formation of these professionals and, in the room chapter, I demonstrate the methodology used to develop the inquiry. In the second part of the work I present a characterization of the education and of the teachers' formation in Brazil and in Portugal. Already in the third and last part, I present the analysis of some legal Brazilian and Portuguese documents that indicate the necessity of an attention the multiculturalidade in the education of these countries and detach some advancements and retreats in this discussion.